Analysis Of Form Coefficient For Measuring Gross Tonnage Of Wooden Ship Based On Domestic Meansurment Method Of Indonesia - Habibi Amal; Syamsul Asri; Andi Ardianti; Suandar Baso (EPI International Journal of Engineering, 2020)
Most of the traditional wooden boats in Sinjai and Bone Districts were measured using the domestic measurement method, ship owners with sizes <GT 7 and <GT 30 refused to verify their vessels. Ship owners feel disadvantaged in terms of policies, permits, landing fees, subsidized fuel rations and so on. This study aims to determine the characteristics of the size and shape of traditional wooden ships, analyze and compare the results of the calculation of the gross tonnage (GT) of the ship which is calculated based on the actual size and shape of the ship (real body) with the ship calculated using domestic measurement methods and compiling mathematical equations in determining the value of the ship volume factor based on the main size to calculate the GT. The data processing method was carried out by using the Slovin technique with a population of 49 ship data for the determination of the minimum sample and then entered into the interval class. The results showed that the traditional wooden ships in Sinjai and Bone Regencies have geometric characteristics that are not much different from one another, but the main sizes are quite varied. The larger the main size of the ship, the greater the difference in GT calculations when using the volume factor value based on the domestic measurement method compared to using the volume factor value generated by real body calculations. The formula for the volume factor value (Cb or f) = 0.238 Log ((LBH)1/3) + 0.5134 can be used to determine the volume factor, especially for ships operating in the Sinjai and Bone Regencies as well as an initial reference for measurements by measuring experts ship so that moderate measurement results are obtained.